Optimization of Growth Conditions for the Production of Bacillus subtilis Using Central Composite Design and Its Antagonism Against Pathogenic Fungi - Vehapi, Meyrem; Inan, Benan; Kayacan-Cakmakoglu, Selma; Sagdic, Osman; Ozcimen, Didem (SPRINGER, 2023)
Today, the enhancement of spore yields of Bacillus subtilis has considerable interest and has been widely investigated. In this context, studies have been carried out to improve the spore yield as well as the production amount. In order to perform this, optimization studies are conducted for large-scale production of B. subtilis in bioreactors. The prokaryotic structure, high extracellular production potential, lack of pathogenic activity, well-known fermentation technology and short fermentation time are the prominent advantages for the production of B. subtilis in a bioreactor. The Bacillus species produce a wide variety of antifungal and antimicrobial compounds, making them ideal biological control agents. In this study, first, the growth conditions of the medium were investigated and then optimized using the central composite design approach to achieve the highest productivity for the growth of B. subtilis. In the experiments, the effect of temperature of 25, 30 and 35 degrees C and pH level of 6.0, 7.0 and 8.0 on spore yield was studied. Moreover, the antifungal activity of the B. subtilis culture was investigated against pathogenic fungi: Colletotrichum gloeosporioides, Botrytis cinerea and Aspergillus brasiliensis.
Keywords: Bacillus subtilis; Optimization; Response surface methodology; Bioreactor; Fermentation; SCALE-UP; ANTIFUNGAL ACTIVITY; SPORE PRODUCTION; STRAINS; SYSTEM; Biotechnology & Applied Microbiology; Microbiology